Effect of a mindset training intervention on Bachelor of Science nursing students. - Lewis, Lisa S.; Williams, Cheryl A.; Dawson, Stephanie D. (Collegian, 2022)
The Mindset Model is a framework that supports student success, and has begun to be studied in health professions education including nursing. This study aimed to determine if a mindset training intervention previously successful in an Associate Degree nursing student population would also show benefit for nursing students in a Bachelor of Science program. The study design was quasi-experimental. Participants completed the Williams Inventory of Learning Strategies survey tool before and after an educational intervention consisting of a 1 hour mindset training session. Although mean scores changed in a direction that demonstrated strengthened growth mindset and willingness to remediate after the mindset training intervention, which could represent practical significance, the results did not meet statistical significance. The results of this study may demonstrate that Bachelor of Science nursing students benefit less from mindset training than their Associate Degree counterparts do. Further study with larger samples is recommended.